2011
DOI: 10.15288/jsad.2011.72.917
|View full text |Cite
|
Sign up to set email alerts
|

Are Changes in Financial Strain Associated With Changes in Alcohol Use and Smoking Among Older Adults?

Abstract: ABSTRACT. Objective: This study aimed to assess whether changes in levels of fi nancial strain are associated with changes in alcohol use and smoking among older adults. Method: Multilevel analyses were conducted using longitudinal data from a randomly selected national sample of older adults (N = 2,352; 60% female). The data were collected in six waves during the period of 1992-2006. We estimated associations between within-person changes in levels of fi nancial strain and the odds of engaging in heavy drinki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
69
1
5

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(81 citation statements)
references
References 33 publications
6
69
1
5
Order By: Relevance
“…Although this study highlights the correlations between poverty and beliefs about smoking and quitting, it does not shed light on whether poverty itself is a risk factor for particular tobacco beliefs or merely a marker for other risks. For example, poverty is a marker for fi nancial strain, and there is a direct association between changes in level of fi nancial strain and probability of smoking (Shaw et al, 2011). Further, within a predominantly lower socioeconomic sample of smokers, baseline fi nancial strain predicted lower rates of abstinence for participants in smoking-cessation treatment (Kendzor et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Although this study highlights the correlations between poverty and beliefs about smoking and quitting, it does not shed light on whether poverty itself is a risk factor for particular tobacco beliefs or merely a marker for other risks. For example, poverty is a marker for fi nancial strain, and there is a direct association between changes in level of fi nancial strain and probability of smoking (Shaw et al, 2011). Further, within a predominantly lower socioeconomic sample of smokers, baseline fi nancial strain predicted lower rates of abstinence for participants in smoking-cessation treatment (Kendzor et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Stable employment has been linked with moving from smoking into non-smoking, although the same study found no association of changes in individual or household income with changes in smoking behaviour 17. Increasing exposure to financial strain (a similar measure to deprivation) has been demonstrated to be associated with a higher likelihood of smoking, particularly among the young–old generation (65–74 years old) 20. But overall evidence on the association between changes in employment status, income and deprivation on changes in smoking seems to be scarce.…”
Section: Introductionmentioning
confidence: 97%
“…Financial strain also places older adults, especially older women, at higher risk for heavy drinking. 16 What is different about alcohol use in older adults compared with younger adults? Agingrelated biological and physiologic changes affect alcohol absorption, metabolism, and elimination.…”
Section: Etiology and Risk Factorsmentioning
confidence: 99%